Constitutional Comparison Between Indonesia And Switzerland Constitutions Regarding The Mechanism Of Constitutional Amendment - Muhammad Zulhidayat (Universitas PGRI Madiun, 2021)
The constitution is often equated with the Basic Law, each State has its own characteristics in drafting their Constitution, the Constitutional differences between one State and another also have an impact and influence the constitutional amendment system of each State. The purpose of this article is to find out how the comparison of the constitutions of Indonesia and Switzerland is related to the mechanism for amendment the constitutions of the those State. The results of this study indicate that in changing the constitution Indonesia must have 2/3 members of the MPR. Meanwhile, Switzerland in making amendment to their constitution gives the people veto rights to participate in determining amendment to their State's constitution. The conclusion in this study is that the Indonesian constitution is more rigid than the Switzerland constitution, the rules regarding amendment to the constitution that are rigid after the fourth amendment can be returned as the rules for changing the constitution before the amendment are more flexible, this will have a positive effect on the constitutional system in Indonesia. The writer's suggestion in this paper is that the Executive and Legislative Institutions immediately make a fifth amendment to replace outdated rules and strengthen the existing government system in Indonesia